Análise da evasão em um curso de licenciatura em matemática da Universidade Tecnológica Federal do Paraná - Oliveira, Jocilene Cristina de (2019)
Considering the expansion of the number of federal universities in Brazil and, consequently, the increase in the number of places in higher education, there have also been increased concerns about discussing the evasion of higher education students. Some universities, such as the Federal Technological University of Paraná, have permanent commissions for these types of studies, but evasion can be a very specific phenomenon of the region where the university is located, type of course and public served. In this sense, the objective of this work is to study the evasion of the students of the Mathematics Degree Course of the Federal Technological University of Paraná, Campus Cornélio Procópio. For this, a case-control study was conducted, in which the cases were the students evaded and the controls the students not evaded. Therefore, it was considered a sample of 93 students and a series of variables studied, obtaining as a result, that the variables marital status, age and participation in projects were significant. Therefore, a student who is married or has a stable union, above 24 years of age and who does not participate in projects, characterizes the profile of students who are more likely to evade.